2005
DOI: 10.1149/1.1921127
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Polymerization of Vinyl Ethylene Carbonate in Li-Ion Battery Electrolyte

Abstract: A study of the anodic oxidation of vinyl ethylene carbonate (VEC) was conducted with post-mortem analysis of reaction products by ATR-FTIR and gel permeation chromatography (GPC). The half-wave potential (E 1/2 ) for oxidation of VEC is ca. 3.6 V producing a resistive film on the electrode surface. GPC analysis of the film on a gold electrode produced by anodization of a commercial Li-ion battery electrolyte containing 2 % VEC at 4.1 V showed the presence of a high molecular weight polymer. IR analysis indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 20 publications
0
44
0
Order By: Relevance
“…A similar chemical to LiDFOB, lithium tetrafluoro oxalato phosphate ͑LTFOP͒, which has only one oxalato ring, was investigated as an alternative salt for lithium-ion batteries. 19,20 As salt, it showed a promising cycling performance as LiPF 6 ; however, the increased surface impedance was has concern because it might affect the power capability of the Li-ion battery. The merit of LTFOP could be retained while the disadvantage could be limited when it is used as a functional additive in the electrolyte with only a few percent of additions.…”
Section: ͓1͔mentioning
confidence: 99%
See 2 more Smart Citations
“…A similar chemical to LiDFOB, lithium tetrafluoro oxalato phosphate ͑LTFOP͒, which has only one oxalato ring, was investigated as an alternative salt for lithium-ion batteries. 19,20 As salt, it showed a promising cycling performance as LiPF 6 ; however, the increased surface impedance was has concern because it might affect the power capability of the Li-ion battery. The merit of LTFOP could be retained while the disadvantage could be limited when it is used as a functional additive in the electrolyte with only a few percent of additions.…”
Section: ͓1͔mentioning
confidence: 99%
“…To overcome this problem, researchers have developed several passivation additives that can polymerize and form a stable passivation film at the electrode surface during the formation cycles. Examples of these additives are vinyl ethylene carbonate, [6][7][8] vinylene carbonate, 7,9-11 lithium bis͑oxalato͒borate ͑LiBOB͒, 12,13 and vinyl pyridine.14 It has been reported that the bis͑oxalato͒borate anion ͑BOB − ͒ of LiBOB can be reduced at 1.7 V vs Li + /Li and form an artificial and stable solid electrolyte interface ͑SEI͒ layer that can improve the capacity retention of graphite negative electrodes. 12,13 Although not yet confirmed, BOB − is believed to be first reduced at 1.7 V vs Li + /Li, after which an oxalato ring forms…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, 1,3-butadiene is cheap and easily available from industry. BMO is readily used to prepare vinylethylene carbonate (VEC), which can largely improve the performance of the secondary battery as an additive [9]. During the synthesis of VEC, carbon dioxide reacts with BMO and is consumed.…”
Section: Introductionmentioning
confidence: 99%
“…These studies allowed identifying important reflections bands of the SEI as the asymmetric carbonyl stretching at 1650 cm FTIR studies on samples from Post-Mortem analyses have also been conducted aiming to tackle differences when using electrolyte additives. [172][173][174] In these cases both, anodes and cathodes were studied. Likewise, FTIR results are used to compare SEI characteristics when changing the Li-based salt.…”
mentioning
confidence: 99%